FACTORS AFFECTING AGROFORESTRY FARMERS’ CAPACITY SURROUNDING NATIONAL PARK - Suyadi Suyadi; Sumardjo Sumardjo; Zaim Uchrowi; Prabowo Tjitropranoto (Indonesian Journal of Forestry Research, 2019)
The rural communities living around the National Park are generally farmers. They are less empowered and classified as poor. This is due to the relatively low capacity of farmers. In order to be more empowered, the farmers need to improve their capacity. This study aimed to analyze the factors that directly and indirectly affect the capacity building of agroforestry farmers around the National Park. This study was conducted in Kuningan and Majalengka districts of West Java Province for four months, from July to October 2017. Sampling technique used was random sampling with cluster location was agroforestry Forest Farmer Group (FFG) in the buffer zone of Gunung Ciremai National Park. The sample size was 310 members of agroforestry Forest Farmer Group. The results showed that the capacity of agroforestry farmers around the National Park was low. This is due to the low level of formal education, farming experience, cosmopolitan level, and narrow farmland of farmers. It is also caused by low environmental support factors (economic accessibility, ecological conditions, FFG role) and low participation of farmers in agroforestry both economically and socially.